TransUnion’s Transformation of Article III Standing and the Implications Post-Dobbs - Miranda Drakes (Washington University Journal of Law and Policy, 2024)
Over the past half-century, the Supreme Court has engaged in a trend of inserting new requirements into standing doctrine, the constitutional doctrine limiting federal court jurisdiction. As a result, fewer and fewer plaintiffs are able to recover for injuries suffered. Through its decision in TransUnion LLC v. Ramirez, the Supreme Court further narrowed standing doctrine by preventing individuals from bringing suit in federal court to enforce rights created by Congress if the rights deviate too far from those traditionally recognized as providing the basis for a lawsuit. This Comment explores the consequences of TransUnion through the lens of the rights impacted by Dobbs v. Jackson Women’s Health Organization and suggests an avenue through which Congress can combat the impingement on its power to recognize new rights and injuries.
Keywords: StandingDoctrine; TransUnionCase; SupremeCourt; CongressionalPower; DobbsDecision